PERLOCUTIONARY ACT OF THE VERBAL VIOLENCE AGAINST WOMEN IN INDONESIA (TINDAK PERLOKUSI KEKERASAN VERBAL TERHADAP PEREMPUAN DI INDONESIA) - Ike Revita; Rovika Trioclarise; Nila Anggreiny; Farah Anindya Zalfikhe (Jurnal Gramatika, 2020)
What people say can bring about some reactions. These reactions are called a perlocutionary act.  This paper is aimed at describing the perlocutionary act of verbal violence against women.  The objective of this writing is to identify the perlocutionary acts of  the women as the victims of the violence verbally. The data were taken in DKI Jakarta and Sumatera Barat by using interviews, note-taking, recording, and questionnaires. There were around women as 30 respondents. These women were the victims of verbal violence domestically.  The analysis was done by using the concept of speech act and verbal violence against women. The result of the analysis was descriptively and narratively done. Besides, the percentage was also used to highlight the number of occurrences of a certain perlocution.  Having analyzed the data, it is found that there are two general reactions as the perlocution of the women, victims of verbal violence domestically. They are 1) arguing, 2) replying with the same words, 3) groveling,  and 4) saying nothing but doing something like crying or being silent. ‘Saying nothing’ occurs more than others because the women surrendered with the circumstances that are also in line with the cycle of the violence itself.